Ant Lion Optimizer for Optimal Reactive Power Dispatch Solution - Rebecca Ng, Shin Mei; M. H., Sulaiman; Zuriani, Mustaffa (JES, 2015)
This paper proposes the application of the recent meta-heuristic method namely Ant Lion Optimizer (ALO) in solving Optimal Reactive Power Dispatch (ORPD) problem. The objective is to minimize the transmission losses by finding the best combination of control variables including generator voltages, transformer tap ratios and reactive compensation devices. In order to show the effectiveness of ALO in solving ORPD, IEEE 30-bus system is utilized. The comparison with other methods also reported in this paper.